Penerapan Teori Belajar Behavioristik dalam Pembelajaran - Prasetyo, Chiyokuna Mukholis Aji (TSAQOFAH, 2024)
Representation is a student’s ability to communicate mathematical ideas or thoughts learned in a certain way. Mathematical representation abilities can help students build concepts and express mathematical ideas, as well as make it easier for students to develop their abilities. Representation can help students to organize their thinking. Mathematical representation is learning that demands optimal mental activity of students in understanding a concept. The aim of this research is to find out how elementary school students use mathematical representation. Representation plays an important role in efforts to develop and optimize students’ mathematical abilities. The concept of mathematical representation learning is a concept that refers to an approach to students through emphasizing the importance of understanding and using various forms of representation to facilitate students’ understanding of mathematics.